EXPERIMENTAL FISHING OFF ULLAL (MANGALORE) - Prabhu, M S; Ramamurthy, S; Kuthalingam, M D K; Dhulkhed, M H (Indian Journal of Fisheries, 2011)
Though an average of 1685 tonnes* of fish is landed annually by the mechanisedboats of Mangalore, which operate during late October to early Maywithin the 25 meter region, no information is available on the abundance, catchcomposition and distribution of the fishery of this area. Hence, experimentalfishing was undertaken at 12 and 25 meters off UUal and the results are piesentedhere which may be of use for commercial exploitation of the fishery of this region-The earlier accounts on the exploratory fishing, however, relate to certain otherparts of the west coast of India (Srivatsa, 1953a, b\ Gopinath, 1954; Jayaramanet al., 1959) except for a brief report on shrimp trawling conducted for four weeksin March/April of 1955 and 1956 between depths of 2 and 10 meters off Mangalore(Shariff, 1959).